Analysis Of Sharia Economic On Forex Trading Of Financial Broker Succes Traders - Gusmansyah, Wery; Ibrah ‘Alamm, Ajeng (CV. Inara, 2022)
There are two issues studied in this thesis: (1) How to Trade Forex on a Financial Broker Succes Trader, (2) How to Analyze Sharia Economic Law on Forex Trading at a Financial Broker Succes Trader. This thesis aims to find out how to trade Forex on a Financial Broker Success Trader and the analysis of sharia economic law on Forex Trading at a Financial Broker Success Trader. This research is a type of field research with empirical normative research methods. From the results of this study, it was found that: (1) Forex Trading on a Financial Broker Success Trader has three aspects, namely; a forex trading contract made with the approval of both parties by filling in personal data before creating an FBS account, forex trading procedures on FBS from how to sell and buy, how to withdraw funds (profits and deposits) and how to freeze a temporary account for traders. Then regarding the object of forex trading transactions on FBS, namely by trading currency pairs of different types. (2) The analysis of sharia economic law on forex trading contracts on FBS is following the provisions of sharia economic law that forex trading is also called al-sharf, namely buying and selling foreign currencies and not trading in similar currencies at different prices but in different currencies at a different rate or value. Forex trading is the same as buying and selling in general, and there is nothing prohibited in Islamic economic law. The procedure for forex trading on FBS is also appropriate regarding how to sell, buy, and withdraw funds and does not include prohibitions in sharia economic law. Regarding the object of forex trading transactions on FBS, it follows the provisions of sharia economic law, namely not trading goods of the same value at different prices but foreign currencies (different types) with different prices.